Implementation of Problem Based Learning (PBL) Learning Model in Mathematics Subjects at Madrasah Ibtidaiyah - Purwandari, Wahyu (EDUCARE: Journal of Primary Education, 2023)
Learning mathematics is a scourge for students; mathematics is considered difficult and scary, so it takes effort from a teacher to achieve the expected goals and fun. Mathematics requires a learning model to help students feel comfortable and happy; it is no longer a lesson they fear but a subject of interest. This study aims to provide solutions to students to follow the learning maximally and according to the goals to be achieved. This study is a type of qualitative descriptive research. The subjects in this study were teachers in MI Darussa'adah Domasan Kalidawir Tulungagung—data collection methods using observation, interviews, and documentation. Data analysis techniques used are data reduction, data presentation, and conclusion. The results of this study explain that mathematics teachers apply the PBL model with several steps according to PBL syntax. Teachers experience several obstacles in using the Problem-Based Learning model, namely, lack of learning resources, lack of students' literacy skills, and limited time. However, the problem-based learning model has advantages in improving mathematics learning activities, including achieving goal activities so students can receive and achieve the target reference value or KKM.